2019
DOI: 10.1007/s12640-019-00033-x
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinogen-Like Action of the Novel Designer Drug 25I-NBOMe and Its Effect on Cortical Neurotransmitters in Rats

Abstract: NBOMes are N-benzylmethoxy derivatives of the 2C family hallucinogens. 4-Iodo-2,5-dimethoxy-N-(2-methoxybenzyl)phenethylamine (25I-NBOMe) is one of the commonly used illicit drugs. It exhibits high binding affinity for 5-HT 2A/C and 5-HT 1A serotonin receptors. Activation of 5-HT 2A receptor induces head-twitch response (HTR) in rodents, a behavioral marker of hallucinogen effect in humans. There is not much data on neurochemical properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 66 publications
8
38
0
Order By: Relevance
“…Therefore, these results suggest that this compound has a common and alarming feature with them. These results are in line with previous studies showing an increased ex vivo striatal DA levels (Jeon et al, 2019) as well as an increased DA transmission in cortical areas of male rats (Herian et al, 2019). Moreover, 25I-NBOMe seems to act differently on DA and 5-HT levels in male and female rats, highlighting sex differences that might influence the frequency of ingestion, as well as the psychoactive effects and the long-term effects.…”
Section: I-nbome Affects the Dopaminergic Transmission In The Nac Ssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, these results suggest that this compound has a common and alarming feature with them. These results are in line with previous studies showing an increased ex vivo striatal DA levels (Jeon et al, 2019) as well as an increased DA transmission in cortical areas of male rats (Herian et al, 2019). Moreover, 25I-NBOMe seems to act differently on DA and 5-HT levels in male and female rats, highlighting sex differences that might influence the frequency of ingestion, as well as the psychoactive effects and the long-term effects.…”
Section: I-nbome Affects the Dopaminergic Transmission In The Nac Ssupporting
confidence: 92%
“…The MDMA-like action of 25I-NBOMe has been also confirmed in vitro since it acts inhibiting the monoamine reuptake transporters with different IC 50 (hSERT, IC 50 = 4.3 µM; hDAT, IC 50 = 75 µM; hNET, IC 50 = 19 µM) in HEK 293 cells (Zwartsen et al, 2017). Recently, it has been demonstrated that this compound increases dopamine (DA) and serotonin (5-HT) in the frontal cortex of male Wistar-Han rats when administered at 3 mg/kg subcutaneously (Herian et al, 2019). Moreover, DA levels in mice synaptosomal striatal fractions were increased by in vitro administration of this substance, and male mice showed an increased conditioned place preference when injected with 25I-NBOMe (0.3 mg/kg, i.p.)…”
Section: Introductionmentioning
confidence: 75%
“…Rodent studies have suggested reinforcing effects for NBOMe derivatives that involve the dopaminergic system (Custodio et al 2019;Seo et al 2019). The NBOMe derivative 4-iodo-2,5-dimethoxy-N-(2-methoxybenzyl)phenethylamine (25I-NBOMe) was shown to increase extracellular dopamine, 5-HT, and glutamate levels in the rat frontal cortex (Herian et al 2019), but unknown are the ways in which these findings translate to humans.…”
Section: Mechanism Of Action Of Phenethylaminesmentioning
confidence: 99%
“…The HTR is widely used as a behavioral marker for hallucinogen effects in humans (Halberstadt and Geyer, 2018). 25C-NBOMe, 25I-NBOMe, and 25B-NBOMe induced an HTR response in rodents with a potency several-fold higher than their 2C counterparts, 2C-C and 2C-I (Halberstadt and Geyer, 2014;Elmore et al, 2018;Custodio et al, 2019;Herian et al, 2019). Two lines of evidence support a notion that this behavioral effect is mediated by cortical 5-HT 2A receptors.…”
Section: Pharmacology Of Nbomesmentioning
confidence: 89%
“…DOI also increased the dopamine level in the cortex and ventral tegmental area (VTA) (Bortolozzi et al, 2005;Pehek et al, 2006). Recently, Herian et al (2019), using microdialysis in freely moving male Wistar-Han rats, demonstrated increased extracellular levels of glutamate, dopamine, and 5-HT in the frontal cortex after administration of 25I-NBOMe. The drug also increased the tissue content of 5-HT and its metabolite hydroxyindoleacetic acid (5-HIAA) but did not affect the tissue content of dopamine and its metabolites: 3,4-dihydroxyphenylacetic acid (DOPAC) and homovanilic acid (HVA).…”
Section: Pharmacology Of Nbomesmentioning
confidence: 99%